Penerapan Virtual Learning Terhadap Hasil Belajar Siswa Madrasah Ibtidaiyah Kota Langsa Pada Masa Pandemi Covid-19 - Junaidi; Suhelayanti; Yusaini (Al-Azkiya: Jurnal Pendidikan MI/SD, 2023)
The implementation of education cannot be hindered by anyone and under any circumstances. Currently, many countries in the world experience obstacles and difficulties in implementing the education process. This is because the world or countries are experiencing the Covid-19 pandemic. So that it threatens various processes of implementing state programs, including the process of implementing education, the most effective thing at this time has been to try to implement the learning process using distance or online methods. Virtual learning mode is a popular method implemented today. Because with this method, students can stay at home, but still actively participate in the learning process. This study aims to determine. Does the adoption of virtual learning have any effect on the academic performance of Madrasah Ibtidaiyah (MI) students in Langsa town? This study is a quantitative study on the whole population including all students of 3 MIs of Langsa city, specifically Madrasah Ibtidaiyah Negeri 1 Langsa City, MI Negeri 2 Langsa City and Madrasah Ibtidaiyah Terpadu Langsa class V who are actively study during the school year of an even semester 2020/2021 Sampling was carried out using the corresponding stratified random sampling technique. Based on the research results, it was found that there was an influence of virtual learning on the academic performance of MI students in Langsa City during the Covid-19 period. This can be seen from the R Square value of 0.059, meaning the influence of the independent variable (virtual learning) on ​​the dependent variable (learning outcomes) is 5.9%.The remaining 94.1% were influenced by other factors not included in this study.The obtained significance value is 0.061 > 0.05, so it can be concluded that the virtual learning variable (X variable) does not have a significant effect on learning outcomes (Y variable).This means that virtual learning had a positive but insignificant impact on the academic performance of MI students in Langsa City during the Covid-19 period.